Estudio fitoquímico y biológico de los componentes fenólicos de la corteza de Geoffroea decorticans - Pastoriza, Ana Cristina (2023)
The stem bark of Geoffroea decorticans (Gill.ex Hook. etArn.) Burk. was used medicinally to cure several skin affections; however, phytochemical and biological antecedents were not found. Analyses of purified methanolic extract from G. decorticans bark (PFGB), realized by silylation derivatization for GC/MS, C18-CC and HPLC followed by two-dimensional TLC and UV-Vis spectroscopy, allowed to characterize nine phenolic compounds, among these, two methoxy flavonoids. Antibacterial assays of PFGB showed the highest activity (MICs = 125 μg/mL) against Staphylococcus aureus (25923) and Enterococcus faecalis (29212) ATCC strains. Moreover, PFGB showed the highest intracellular antioxidant activity at low concentration (5 μg/mL), evaluated by using the fluorescent DA-H2DCF probe on lymphocyte culture; cytotoxic effects on lymphocytes activated or not by LPS were not observed, through Trypan Blue Exclusion and MTT colorimetric assays. The results obtained from the ethnomedicinal approach of this work contribute to the scientific validation of the vulnerary medicinal use of G. decorticans.